Capital and Exploitation - Weeks, John, 1941- (Book collections on Project MUSE., 2014)
Professor Weeks proposes that the key to Marx's critique of capitalist society is the labor theory of value. A commodity-producing society, he argues, necessarily gives rise to a capitalist society, so that commodity production and the exploitation of labor are inseparably linked. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books.